Cranial ultrasound findings in well newborn Ugandan infants. Issue 5 (20th May 2010) - Hagmann, CF; Robertson, NJ; Acolet, D; Chan, D; Onda, S; Nyombi, N; Nakakeeto, M; Cowan, FM
Abstract : Background: There has been no study assessing cranial ultrasound (cUS) scans in newborn infants born in equatorial Africa. Objective: To assess the cUS scans of apparently well newborn term Ugandan infants and to correlate the findings with perinatal data. Methods: An observational study of apparently healthy postnatal ward term Ugandan infants at Mulago Hospital, Makerere University Hospital, Kampala, Uganda. Results: Data from 112 infants scanned at a median age of 1.4 postnatal days were analysed. Only 57 (51%) infants had scans considered normal, including 30 infants with isolated focal peritrigonal white matter (WM) echogenicity that was very common, occurring in 60 (53%) of infants. More extensive WM echogencities were seen in nine (7.5%) and focal unilateral central grey matter echogenicity in eight (6.5%) infants. Haemorrhage was not common. Subependymal pseudocysts (SEP) and choroid plexus cysts (CPC) occurred in 19.6% of infants each. Four infants only had lenticulostriate vasculopathy. No correlation was found between mode of delivery, birth weight, head circumference or gestational age, maternal HIV status and any cUS abnormality. Conclusions: Apparently well term-born Ugandan infants frequently have abnormalities on cUS. These are mainly increased WM echogenicity, SEP and CPC. These may relate to the reported high incidence of congenital infections in this population but this remains to be confirmed. The observations provide baseline data for comparison with scans from sick infants from similar communities and are also important for studies in which cUS will be used to assess progress.